2019
DOI: 10.1037/dev0000706
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the development of face and emotion processing under a predictive processing framework.

Abstract: In the present work, we explore the development of processing of emotional facial configurations under a Predictive Processing (or Predictive Coding) framework. Predictive Processing provides a new approach to brain function that has been used to explain a wide range of processes, from perception to socio-emotional processing. The explanatory power of this framework for adult brain function is widely recognized, but it has yet to be systematically applied to understanding the developing brain. Studying the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 156 publications
(225 reference statements)
0
20
0
Order By: Relevance
“…In recent years, there has been a growing interest in interoception in psychology and neurosciences, as this construct has provided valuable insights to understand cognition and fine-tune theories of neural functioning (e.g., Critchley & Harrison, 2013;Seth & Friston, 2016). Interoception has also been linked to processes such as visual perception and action states (Marshall et al, 2017(Marshall et al, , 2018, as well as with higherorder cognitive domains, such as emotion processing (Barrett, 2016;Pereira et al, 2019) and social cognition (Fotopoulou & Tsakiris, 2017;Ondobaka et al, 2017). Furthermore, interoception has been implicated in a wide range of psychiatric conditions (e.g., mood and anxiety disorders) and transdiagnostic traits such as alexithymia (Khalsa et al, 2018;Murphy et al, 2017;Trevisan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in interoception in psychology and neurosciences, as this construct has provided valuable insights to understand cognition and fine-tune theories of neural functioning (e.g., Critchley & Harrison, 2013;Seth & Friston, 2016). Interoception has also been linked to processes such as visual perception and action states (Marshall et al, 2017(Marshall et al, , 2018, as well as with higherorder cognitive domains, such as emotion processing (Barrett, 2016;Pereira et al, 2019) and social cognition (Fotopoulou & Tsakiris, 2017;Ondobaka et al, 2017). Furthermore, interoception has been implicated in a wide range of psychiatric conditions (e.g., mood and anxiety disorders) and transdiagnostic traits such as alexithymia (Khalsa et al, 2018;Murphy et al, 2017;Trevisan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies emphasize the role of attachment figures, with whom one could appropriately place epistemic trust (Fonagy and Allison, 2014), in the progressive refinement of the internal self-model via predictive processing mechanisms, in the course of psychological development (Palmer et al, 2015;Fotopoulou and Tsakiris, 2017;Pereira et al, 2019). In accordance, in cases of insecure attachment, the possibilities for active (or enactive) inference are compromised due to the absence of a secure base for exploration.…”
Section: The Development and Use Of A Predictive Brain In The Therapeutic Realmmentioning
confidence: 99%
“…The differences that we found among mothers experiences (in the case of a fullterm, preterm and very preterm birth) need to be addressed in providing care for these families. Moreover, evidence suggests that the first experiences of contact with the world are especially relevant for infant's later socio-emotional development, namely it has been found that early social experience affects the developing brain and thereby infants social, cognitive, and emotional development [63]. Infants' early postnatal period is characterized by heightened brain plasticity and, in particular, high sensitivity to social environmental influences [64].…”
Section: Summary Of Findings General Reflections and Clinical Implicmentioning
confidence: 99%